DEVELOPMENT OF PSYCHOMOTOR APTITUDE - THE BALANCE - BY EXERCISES SPECIALLY CREATED WITHIN THE FRAMEWORK OF THE BASKETBALL DISCIPLINE IN THE 5TH AND 6ᵗʰ FORMS PUPILS - Adrian PAŞCAN; Ioan PAŞCAN (Cluj University Press, 2015)
Due to the importance of the ability - balance - in the basketball game, this paper presents a series of exercises for improving this psychomotor skills. During the first phase specific exercises as responses to different signals were conceived under our guidance with the entire class, which were then practiced. During a second phase, after having understood the task, the children split into teams needed to conceive similar exercises. The most significant were then practiced with the entire class. The research had been comprised of four phases: a pretest, a test during which independent variables were applied, followed by a final evaluation, and at the end a final test. The results of the research have shown that the exercises used contributed to the improvement of balance and we recommend that they should be used during physical education classes, mentioning that these are to be adapted and even supplemented according to the age of the children, the existing infrastructure and their training level. This paper presents the most significant exercises conceived and applied to the trial group. Exerciții pentru dezvoltarea aptitudinii psihomotrice - echilibrul - prin exerciții special create în cadrul disciplinei baschet la clasele V-VI. Datorită importanței în jocul de baschet a echilibrului, această lucrare prezintă o serie de exerciții care să dezvolte această aptitudine. În prima fază, sub îndrumarea noastră, au fost concepute și s-au exersat exerciții specifice, urmând ca, în faza a doua, după înțelegerea sarcinii, elevii împărțiți în formații de lucru să conceapă exerciții analoage, cele mai semnificative fiind exersate cu toată clasa. Cercetarea a cuprins patru etape: un preexperiment, un experiment în care s-au aplicat variabilele independente, urmate de o evaluare finală, iar la sfârșit un retest. Rezultatele cercetării ne-au demonstrat faptul că exercițiile folosite au contribuit la dezvoltarea echilibrului și recomandăm utilizarea lor în lecțiile de educație fizică, cu precizarea că aceste exerciții să fie adaptate și chiar completate în conformitate cu vârsta elevilor, baza materială existentă și nivelul lor de pregătire. Lucrarea de față prezintă cele mai semnificative exerciții create și aplicate lotului experimental. Cuvinte cheie: experiment, echilibru, exerciții specifice, aptitudine psihomotrică.